Parents and teachers roles in preschool children’s education in Kenya. How can it be defined? - Koech, Peter K. (Asia Pacific Journal of Education, Arts and Sciences, 2014)
This paper analyses the roles of parents and teachers in preschool education in Uasin Gishu County, Kenya. The paper argues that in spite of the Kenyan government effort to strengthen parent-teacher partnerships, partnerships in early childhood education in Kenya in still low. This article argues that most parents and even teachers and other stakeholders in preschool are ignorant of the roles they need to play in the partnerships. The study uses data collected for a doctoral dissertation study findings in Uasin Gishu County. The purpose of this study was to explore parents’ teacher roles in children’s education. This study used an Ex Post Facto design. The target populations were parents and teachers of preschool, pre-school and primary school Headteachers and MOE officials. The sample size consisted of 135 parents, 60 teachers, 10 Head teachers and 10 MOE Officials. Questionnaires and interview schedules were used for data collection. Means, percentages formed part of the descriptive statistics. ANOVA and t-test of independent samples were used and null hypotheses were tested at alpha value 0.05. Findings revealed that parents, teachers, head teachers and MOE officials differed significantly in some modes of parent-teacher partnerships. All this is partly because of ignorance of the roles that parents and teachers define for themselves among others. The main argument is that the Kenyan government and stakeholders must unite in promoting parent-teacher partnerships for the betterment of children’s education and holistic development. It was recommended that there is need to highlight the roles stakeholders should play in early childhood education for harmonious working relationships in schools.
Keywords: Uasin Gishu County; Role definition; Parent-teacher partnerships; Pre-school Stakeholders